The effect of macro variables on Indonesian stock exchanges in pandemic COVID-19 - Roziq, Teuku Adya; Shukri, J M; Kusairi, Suhal; Sanusi, Nur Azura (Asian Journal of Economic Modelling, 2024)
During the COVID-19 pandemic, it is crucial for stock traders inside a specific nation to conscientiously examine and assess the current monetary conditions and macroeconomic data. This study examined the influence of macroeconomic factors, namely unemployment, inflation, interest rates, and exchange rates, on the Indonesian stock market index within the framework of the COVID-19 pandemic. This research employs quantitative approaches, notably autoregressive distributed lag (ARDL) analysis, to evaluate the dynamics of time series data. The current analysis shows that a variety of factors, such as inflation, interest rates, and exchange rates, have an impact on the stock price index. Furthermore, the results of this study indicate that the deviation from the long-term equilibrium in the short term is rectified at a monthly rate of 33.47%. As a result of completing an exhaustive analysis of this study, it is of the utmost importance for the Indonesian government to concentrate its attention on the issues of unemployment, inflation, interest rates, and currency rates during the COVID-19 epidemic. This is done with the intention of achieving stability on the stock exchange. In addition, it is strongly suggested that investors do a comprehensive analysis of the volatility of stock prices by incorporating a variety of macroeconomic elements.